1983
DOI: 10.1039/c39830000862
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the diphosphene ArPPAr (Ar = 2,4,6-But3C6H2) with sulphur: isolation and X-ray structure of the diphosphene monosulphide

Abstract: The diphosphene ArP=PAr (Ar = 2,4,6-But3C6H2) reacts with elemental sulphur to give the stable monosulphide ArP(S)=PAr (2) whose structure was confirmed by an X-ray analysis; when treated with hexamethylphosphorous triamide, (2) reverts to the starting diphosphene but thermal and photochemical isomerisation of (2) gives the thiadiphosphirane ArP-S-PAr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…In contrast to the sulfurization reaction of Mes * P PMes * reported by Yoshifuji et al [18,19], the corresponding diphosphene monosulfide derivatives, TbtP P( S)Tbt and TbtP P( S)Fc, were not observed during these reactions as judged by 31 P NMR spectroscopy.…”
Section: Reactions Of Diphosphenes 1a and 1b With Elemental Sulfurcontrasting
confidence: 82%
See 2 more Smart Citations
“…In contrast to the sulfurization reaction of Mes * P PMes * reported by Yoshifuji et al [18,19], the corresponding diphosphene monosulfide derivatives, TbtP P( S)Tbt and TbtP P( S)Fc, were not observed during these reactions as judged by 31 P NMR spectroscopy.…”
Section: Reactions Of Diphosphenes 1a and 1b With Elemental Sulfurcontrasting
confidence: 82%
“…It was demonstrated that the sulfurization and selenization reactions of diphosphenes should be convenient for obtaining unique heterocyclic compounds such as thia-and selenadiphosphiranes, since the sulfurization reaction of Mes * P PMes * using elemental sulfur in the presence of amine was reported to give the corresponding thiadiphosphirane, Mes * P(S)PMes (2d), as a stable three-membered heterocyclic compound via the corresponding diphosphene monosulfide, Mes * P P( S)Mes * as a metastable intermediate [18,19]. For example, the synthesis of selenadiphosphiranes has been achieved by the treatment of diphosphenes (Mes * P PMes * , Mes * P PMes, Mes = 2,4,6-trimethylphenyl [22], and DisP PDis, Dis bis(trimethylsilyl)methyl [30]) with elemental selenium.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Diphosphene 109 gave a sulfide Ar*-P(S)‫ס‬P-Ar* 111 with S 8 , and 111 was quantitatively converted to thiadiphosphirane 112 by heating or irradiation [109]. The isomerization was supported by the results of an MO calculation [110].…”
Section: From Phosphinidenes (R-p) To Kinetic Stabilization Of Low Comentioning
confidence: 99%
“…Above all, the cycloaddition reactions of such heavier π-bond systems were found to be convenient routes to novel heterocyclic systems. For example, Yoshifuji et al reported that the sulfurization and selenization reactions of Mes*P = PMes* afforded the corresponding chalcogenadiphosphiranes (three-membered ring compounds) as the final products [8][9][10][11][12]. In addition, many examples have been reported for the [2+4]cycloaddition reactions of diphosphenes with dienes giving the corresponding six-membered ring compounds containing a P-P bond [1−4].…”
mentioning
confidence: 99%